Answer:
6.35555556
Step-by-step explanation:
I ain't never seen two pretty best friends
Answer:
5
Step-by-step explanation:
9x+6y=-3
9x+6(-8)=-3
9x-48=-3
9x=45
x=5
Answer:
-6.1
Step-by-step explanation:
Hope this helps!
<u>Zeros of the function</u>
f(x) = (x + 2)² - 25
f(x) = (x + 2)(x + 2) - 25
f(x) = x(x + 2) + 2(x + 2) - 25
f(x) = x(x) + x(2) + 2(x) + 2(2) - 25
f(x) = x² + 2x + 2x + 4 - 25
f(x) = x² + 4x + 4 - 25
f(x) = x² + 4x - 21
x² + 4x - 21 = 0
x = <u>-(4) +/- √((4)² - 4(1)(-21))</u>
2(1)
x = <u>-4 +/- √(16 + 84)</u>
2
x = <u>-4 +/- √(100)
</u> 2<u>
</u>x = <u>-4 +/- 10
</u> 2<u>
</u>x = -2 <u>+</u> 5<u>
</u>x = -2 + 5 x = -2 - 5
x = 3 x = -7
f(x) = x² + 4x - 21
f(3) = (3)² + 4(3) - 21
f(3) = 9 + 12 - 21
f(3) = 21 - 21
f(3) = 0
(x, f(x)) = (3, 0)
or
f(x) = x² + 4x - 21
f(-7) = (-7)² + 4(-7) - 21
f(-7) = 49 - 28 - 21
f(-7) = 21 - 21
f(-7) = 0
(x, f(x)) = (-7, 0)
<u>Vertex</u>
<u>X - Intercept</u>
<u />-b/2a = -(4)/2(1) = -4/2 = -2
<u>Y - Intercept</u>
y = x² + 4x - 21
y = (-2)² + 4(-2) - 21
y = 4 - 8 - 21
y = -4 - 21
y = -25
(x, y) = (-2, -25)
<u />